Parity-time chain of whispering-gallery mode resonators - Phang, Sendy; Vukovic, Ana; Creagh, Stephen; Benson, Trevor M.; Gradoni, Gabriele; Sewell, Phillip D. (2015)
The paper analyses the dispersion characteristics of an infinitely long PT chain made of whispering gallery resonators with gain/loss modulation. The results show that the appearance of the threshold breaking point depends not only on both of coupling and gain/loss modulation but also on the Bloch phase. The Bloch phase is seen as an additional parameter that can reduce or even completely eliminate PT-breaking threshold.